Gilteritinib Enhances Anti-Tumor Efficacy of CDK4/6 Inhibitor, Abemaciclib in Lung Cancer Cells - Sun, Chao-Yue; Talukder, Milton; Cao, Di; Chen, Cun-Wu (Frontiers in Pharmacology, 2022)
Abemaciclib is a cyclin-dependent kinases 4/6 (CDK4/6) inhibitor approved for the treatment of metastatic breast cancer. Preclinical studies suggest that abemaciclib has the potential for lung cancer treatment. However, several clinical trials demonstrate that monotherapy with abemaciclib has no obvious superiority than erlotinib to treat lung cancer patients, limiting its therapeutic options for lung cancer treatment. Here, we show that the US Food and Drug Administration (FDA)-approved drug, gilteritinib, enhances the cytotoxicity of abemaciclib through inducing apoptosis and senescence in lung cancer cells. Interestingly, abemaciclib in combination with gilteritinib leads to excessive accumulation of vacuoles in lung cancer cells. Mechanistically, combined abemaciclib and gilteritinib induces complete inactivation of AKT and retinoblastoma (Rb) pathways in lung cancer cells. In addition, RNA-sequencing data demonstrate that combination of abemaciclib and gilteritinib treatment induces G2 phase cell-cycle arrest, inhibits DNA replication, and leads to reduction in homologous recombination associated gene expressions. Of note, abemaciclib-resistant lung cancer cells are more sensitive to gilteritinib treatment. In a mouse xenograft model, combined abemaciclib and gilteritinib is more effective than either drug alone in suppressing tumor growth and appears to be well tolerated. Together, our findings support the combination of abemaciclib with gilteritinib as an effective strategy for the treatment of lung cancer, suggesting further evaluation of their efficacy is needed in a clinical trial.